THE PURPOSES OF LONGER LIVES: A FOUR-FIELD PERSPECTIVE FROM GSA FELLOWS - Albert, S M (Innov Aging, 2018)
The 2018 GSA Fellows Symposium features distinguished GSA Fellows from each of the four GSA sections: Biological Sciences (BS), Health Sciences (HS), Behavioral & Social Sciences (BSS), and Social Research, Policy & Practice (SRPP). The theme of the 2018 GSA Fellows Symposium is the “Purposes of Longer Lives.” The “purposes” are multiple and require the full range of disciplines in gerontology. From the biological sciences we can ask what governs length of life and integrity of function in late life. From the health sciences we can ask what constitutes meaningful life in advanced age and how to promote meaningful longevity even in the presence of loss of health, including cognitive decrements. From the behavioral and social sciences, we can ask how we can promote self-direction in late life, who is likely to have longer lives, and what allows us to reach late life. Finally, from policy and practice we can ask what investments allow longer lives and what advantages and challenges come with these lives. Presenters include S. Michal Jazwinski, PhD, FGSA (BS), “Purpose is an emergent property of an aging system”; Ann Kolanowski, PhD, RN, FGSA, FAAN (HS), “Well-being in late stage dementia: How will we know it when we see it?”; Kimberly van Haitsma, PhD, FGSA (BSS), “Preference-based Living: Examining older adults’ preferences for everyday living through the lens of research and practice”; and Jon Pynoos, PhD, FGSA (SRPP), “Housing the Aged: Public Policy at the Crossroads.”